Soluble Crosslinked Fibrin(ogen) Polymers - Selmayr, Eberhard; Müller-Berghaus, Gert (Thrombosis and Haemostasis, 1985)
The present study is concerned with the formation of fibrin-fibrinogen associations in the presence of FXIIIa while fibrinolysis was inhibited by aprotinin and EACA. SDS agarose-poly acryl-amide gel electrophoresis on 2.5% gels under non-reducing conditions and ultracentrifugation of the associations on urea-sucrose density gradients showed the formation of soluble crosslinked high molecular weight (HMW) fibrin-fibrinogen polymers with an estimated molecular size up to 10 times that of fibrinogen. After incubation of a mixture of 131I-fibrinogen (4 mg/ml) and 125I-desAA-fibrin (0.2 mg/ml) with FXIIIa (2 U/ml) for 1 h at 37ΰ C, about 5% of the fibrinogen and 80% of the fibrin was incorporated into the generated soluble HMW polymers. The detection of soluble crosslinked fibrin-fibrinogen polymers could be a useful diagnostic criterion for imminent DIC.
Keywords: Soluble fibrin; Fibrinogen; FXIIIa; Prevention of clot formation